LITERASI EKONOMI PADA MASYARAKAT NELAYAN DESA PULAU LEMUKUTAN - okiana okiana; Jumardi Budiman (FKIP Unswagati, 2021)
AbstractThis research was based on the relevant previous of various research results that literacy economic usually obtained from learning formal give a positive role of someone behavior and economic phenomena in the fisherman society in Lemukutan Island Village generally only have primary and secondary education. The purpose of this research is to assess the fishing community's economic literacy in Lemukutan Island Village. Methods used is descriptive quantitative data collection of communication and the indirect impact of the survey data. Respondents to this research of the communities in the Lemukutan Village is 1.024. Sample of this research as much as 258 respondents. Data analysis techniques used that is mean of the economic literacy index. Based on processing the data that has been exercised toward research indicators covering: 1 ) knowledge of the value of goods and scale of the priority in his life budgeting; 2 ), savings and managing money; 3 ) credit management; 4 ) the importance of insurance and protection against a risk; 5 ) investment planning 6 ); the old age pension; and 7) information of products can be expressed that the rate of 54 respondents was 54 percent. That means a literacy level in a stuff literate categories.Keywords: literate, economic, society, fisherman.